Governance of Endowment Institutions and Their Role in Supporting Entrepreneurial Projects in the Sultanate of Oman "An Analytical Comparative Study" - Al-Hamdi, Khalifa Mohammed Khalifa (Journal of Economic, Administrative and Legal Sciences, 2024)
The charitable sector has always been an integral component of the economic structure of leading countries, following the government and private sectors. This study aimed to explore the current state of one of its most prominent components, namely, endowment institutions in the Sultanate of Oman. It also focused on the role of governance in enhancing their administrative and financial performance, as well as strengthening their investments and their ability to provide sustainable quality community services that revolve around modern objectives imposed by economic and social changes, especially in the entrepreneurship sector.The researcher employed the structural-functional approach that included research based on review, analysis, and comparison when addressing the study's topic. The research yielded several findings, among which was that the Sultanate boasts a distinct and exceptional endowment heritage. The government has made progress in governing both public and private endowment institutions, with regulatory and legislative frameworks in place. However, the researcher did not find any public or private endowment institution in the Sultanate that dedicates its revenues toward promoting the fundamental elements of the entrepreneurship sector, despite the social and economic implications of unemployment issues. There are notable models in this sector in the Gulf and Arab regions, which led the researcher to recommend the necessity of governmental intervention using legislative, economic, and administrative tools to transform this sector into one of the wings of the Omani investment apparatus. It is also essential to establish both a public and a private endowment institution dedicated to enhancing, developing, and diversifying development projects in the entrepreneurship sector in the Sultanate of Oman.
Keywords: Governance; Endowment; Governance of Endowment Institutions; Entrepreneurship; Sultanate of Oman